Dietary fatty acids and colorectal cancer risk in men: A report from the Shanghai Men's Health Study and a meta‐analysis. Issue 1 (31st August 2020) - Nguyen, Sang; Li, Honglan; Yu, Danxia; Cai, Hui; Gao, Jing; Gao, Yutang; Luu, Hung N.; Tran, Huong; Xiang, Yong‐Bing; Zheng, Wei; Shu, Xiao‐Ou
Abstract: Evidence from animal models suggests that dietary fatty acids have both anticancer and tumor‐promoting effects. Whether dietary fatty acids are associated with colorectal cancer (CRC) in humans remains inconclusive. We investigated associations between dietary fatty acids and risk of CRC among 59 986 men who participated in the Shanghai Men's Health Study (SMHS), an ongoing population‐based prospective cohort study. We identified 876 incident CRC cases in the SMHS during a mean follow‐up of 9.8 years. Associations between dietary fatty acid intake and CRC risk were evaluated by Cox proportional hazard regression analyses. Consumption of saturated fatty acids (SFA), monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA) was not significantly associated with CRC risk. Multivariate hazard ratios (HRs) and respective 95% confidence intervals (CIs) for Quartile 4 vs Quartile 1 were 0.92 (0.74‐1.14; P trend = 0.47) for SFA, 0.95 (0.79‐1.16; P trend = 0.74) for MUFA and 1.18 (0.95‐1.46; P trend = 0.21) for PUFA. No significant associations were found for total n‐6 PUFA or total n‐3 PUFA. Additionally, we performed a meta‐analysis to summarize results from the present study and 28 reports from 26 additional cohorts, which supported the overall null association between dietary fatty acid intake and CRC risk among men. Docosahexanoic acid and eicosapentaenoic acid were associated with 11% to 12% reduced risk, and linoleic acid a 19% increased risk, of CRC in the meta‐analysis of combined sexes. In conclusion, this population‐based prospective study and meta‐analysis of cohort studies found little evidence that dietary fatty acid intake was associated with risk of CRC in men. Abstract : What's new? While diet is an important factor in colorectal cancer (CRC) risk, the contribution of specific dietary components, particularly dietary fatty acids, to CRC risk remains unclear. In this comprehensive analysis of data from a prospective cohort study and meta‐analysis of 26 additional cohorts, consumption of total, saturated, monounsaturated, or polyunsaturated fatty acids, including specific fatty acids, was not significantly associated with CRC risk in men, overall or by anatomic site. Meta‐analysis of men and women combined revealed a positive association with linoleic acid intake, while eicosapentaenoic acid and docosahexanoic acid were inversely associated with CRC risk.